FACTORS CAUSING POVERTY AND MECHANISMS OF THEIR REDUCTION (American Journal of Business Management, Economics and Banking, 2023)
The mechanism of poverty formation is a complex and dynamic process. Currently, there is no complete theory of research on the factors that form poverty. This article examines the theoretical aspects of poverty-causing factors. Today, various factors causing poverty are analyzed: economic factors, individual factors, social factors, geographical factors, etc.